S116 The quality of copd patient care – outcomes from the british lung foundation patient passport. (12th November 2019) - Philip, KEJ; Gaduzo, S; Rogers, J; Laffan, M; Hopkinson, NS
Abstract : Aim: The British Lung Foundation COPD Patient Passport www.blf.org.uk/passport was developed as a resource to help patients with the condition and clinicians to consider the care they had received and to identify essential omissions. We aimed to use the online data collected to evaluate the delivery of COPD care in the UK from a patient perspective. Method: Each patient passport consists of 13 questions relating to key aspects of COPD care including: spirometry confirmation of diagnosis, understanding their diagnosis, support and a written management plan, vaccinations, smoking cessation, physical activity, exercise, eating well, pulmonary rehabilitation, exacerbations, medications, and yearly reviews. Data were presented as proportions with an answer correspond to good care, and plotted over time to identify trends. Results: After removing duplicates, data from 41, 769 entries, completed online between November 2014 and April 2019, were available (table 1). Only 24% reported receiving support to manage their care and a written action plan; only 53% could spot the signs of an acute exacerbation; only 34% had discussed pulmonary rehabilitation; and only 41% stated they understand their COPD, and their doctor or nurse has explained where to find information, advice and emotional support. A quarter reported not receiving flu vaccination and a third of people with COPD who smoke were not offered support to quit smoking. Even the strongest areas including a spirometry-confirmed diagnosis, and knowing the importance of being active and eating well, achieved only around 80%. Most responses remained stable over time or got slightly worse. Conclusion: Analysis of response to the BLF COPD Patient Passport identifies substantial gaps in the delivery of care. There is little evidence that there has been improvement over the 5 years covered by the data. These patient perspective data provide a unique yet commonly overlooked perspective on care quality, and highlight the need for new approaches if the ambitions set out in the NHS Long Term Plan are to be met.